Analysis of Backhand Stroke Ability among Table Tennis UKM Members - Tafonao, Tison Rahmat; Sugiarto, Bambang Gatot; Zakaria, Dhani Agusni (Journal of Physical and Outdoor Education, 2025)
Thisstudy aimsto analyze the level of backhand stroke ability among members of the Table Tennis UKM at STKIP Pasundan Cimahi. This research uses a quantitative method with a survey approach, employing a skill test instrument in the form of a backhand backboard test. The population consisted of all members of the Table Tennis UKM, with a total sample of 15 participants. The results showed that 60% of participants were in the "very good" category, 27% in the "good" category, and 13% in the "fair" category. It can be concluded that the majority of UKM members possess a high level of backhand stroke ability. These findings are expected to serve as a basis for developing more effective and targeted training programs.